The Political as Presence: On Agonism in Citizenship Education - Tryggvason, Ásgeir (Philosophical Inquiry in Education)

(untitled) (Canadian Philosophy of Education Society, 2017)
In recent years, an agonistic approach to citizenship education has been put forward as a way of educating democratic citizens. Claudia W. Ruitenberg (2009) has developed such an approach and takes her starting point in Chantal Mouffe’s agonistic theory. Ruitenberg highlights how political emotions and political disputes can be seen as central for a vibrant democratic citizenship education. The aim of this paper is to critically explore and further develop the concepts of political emotions and political disputes as central components of an agonistic approach. In order to do this, I return to Mouffe’s point of departure in the concept of the political. By drawing on Michael Marder’s (2010) notion of enmity, I suggest how “the presence of the other” can be seen as a vital aspect of the political in citizenship education. By not abandoning the concept of enmity, and with the notion of presence in the foreground, I argue that Ruitenberg’s definition of political emotions needs to be formulated in a way that includes emotions revolving around one’s own existence as a political being. Moreover, I argue that in order to further develop the agonistic approach, the emphasis on the verbalization of opinions in political disputes needs to be relaxed, as it limits the political dimension in education and excludes crucial political practices, such as exodus.